Within Our Grasp : A World Free of Poverty - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank Group discusses the opportunity to create a world free from the stain of poverty and economic exclusion. He states that the environmental challenge is a fundamental threat to economic development and the fight against poverty in the world. He believes that assuring growth is inclusive is both a moral imperative and a crucial condition for sustained economic development for any country. The World Bank Group is now working on a revamped strategy to significantly strengthen our climate change interventions and help catalyze urgent action among global partners on the scale required. Progress is never inevitable. He concludes by saying that if we act today, if we work relentlessly toward these goals of ending extreme poverty and boosting shared prosperity, we have the opportunity to create a world for our children which is defined not by stark inequities but by soaring opportunities.